Study of bus control strategies by computer simulation. - Chen, Lule. (University of Ottawa (Canada), 1994)
In this thesis, a simulation model used to simulate the running of buses on a single route, OC Transpo route 95, is studied. The model is implemented on a platform different from its original design at the University of Ottawa, and validation experiments are performed. For the most part, the model seems valid, although some additional calibration is recommended. New headway-based bus control strategies are presented and compared with other known control strategies. The statistical analysis and comparisons of those control strategies are based on the testing results obtained from the simulation model. The new headway control policies (called "Message Board" and "hybrid" policies) are shown to provide better service reliability in terms of less variable headway for the high-frequency route 95. Finally, a prototype of a knowledge-based system for real-time bus control purposes is developed and tested on the simulation model. The prototype is shown to be an interesting alternative for real-time bus control: it can effectively interface with the simulation model and perform real-time service control. This prototype will be a building block in the development of a more complete knowledge-based system capable of implementing more complex real-time service control policies in the hope of providing assistance to human controllers.
Keywords: Engineering, Civil.